Nuclear power - Wood, J. (Janet) (Institution of Engineering and Technology, 2007)
This is the first of four new-look books in the Power and Energy series that are aimed at industry professionals rather than academics. This book explains in detail how nuclear power works, its costs, its benefits as part of the electricity supply system. This book covers the debate over the pros and cons of nuclear power. There will be broad market interest in this book, which has been written for general awareness.